Is ‘Sound-Reduplicative Word’ Still a Reduplicative Word or Not? : A Revision from a Study of Academic Documents, Textbook, andThaiOrdinary National Education Test - แซ่เจี่ย, ธงชัย (Parichart Journal, 2017)
Thai textbooks published nowadays both counted and uncounted ‘sound-reduplicative word’ as a part of explanation of ‘reduplicative word’. This article, which is a document research, aims to point the dissension of knowledge about ‘reduplicative word’ and ‘sound-reduplicative word’ by studying 3 groups of documents; which are academic documents that explain Thai grammar, Thai textbooks for grade 7-12 students that mentioned about ‘reduplicative word’, and Ordinary National Education Test during academic year 2006-2016. The result, which is a descriptive analysis, is that three groups of documents show the dissension of knowledge about ‘sound-reduplicative word’ in present Thai teaching. ‘Sound-reduplicative word’ used to present in some academic documents in the past, but it is uncounted as a part of Thai grammar nowadays. It is harmonized with ‘reduplicative word’ appeared in Thai Ordinary National Education Test, which is non-specific on ‘sound-reduplicative word’, but ‘reduplicative word’ appeared in the test mostly are ‘reduplicative word’ which related both sound and meaning. However, some Thai textbooks still explain ‘sound-reduplicative word’ as a part of ‘reduplicative word’. The inconsistence of knowledge about ‘sound-reduplicative word’ leads to a question about ‘reduplicative word’ teaching in the future.